Inclusive Open Educational Resources (iOER) Showcase: Participation by the Faculty of Cognitive Sciences and Human Development at Universiti Malaysia Sarawak - Julia Ai Cheng, Lee (UNIVERSITI MALAYSIA SARAWAK, 2024)
The Ministry of Higher Education (MOHE), in collaboration with the United Nations Educational, Scientific and Cultural Organization (UNESCO) and Majlis E-Pembelajaran Institusi Pendidikan Tinggi Awan Malaysia (MEIPTA), organized an Inclusive Open Educational Resources (iOER) showcase on 18 January 2024. The iOER showcase was officiated by Professor Dr. Azlinda Azman, the Director General of Higher Education, Ministry of Higher Education.